2022
DOI: 10.1111/ene.15534
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of nerve ultrasonography for the detection of peripheral neuropathy in type 2 diabetes

Abstract: Background and purpose Nerve conduction studies (NCS) are the current objective measure for diagnosis of peripheral neuropathy in type 2 diabetes but do not assess nerve structure. This study investigated the utility of peripheral nerve ultrasound as a marker of the presence and severity of peripheral neuropathy in type 2 diabetes. Methods A total of 156 patients were recruited, and nerve ultrasound was undertaken on distal tibial and distal median nerves. Neuropathy severity was graded using the modified Toro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…We congratulate the authors for their great effort in evaluating the specificity and sensitivity of tibial nerve ultrasound imaging for the diagnosis of neuropathy in type 2 diabetes. Indeed, the authors have demonstrated the correlation between the tibial nerve cross-sectional area (CSA) and the severity of neuropathy [1]. Herein, we would like to comment on their Figure 2 which represents transverse ultrasound imaging to measure the tibial nerve CSA.…”
Section: Hindsight For Ultrasound Imaging/measurement Of the Tibial N...mentioning
confidence: 99%
See 2 more Smart Citations
“…We congratulate the authors for their great effort in evaluating the specificity and sensitivity of tibial nerve ultrasound imaging for the diagnosis of neuropathy in type 2 diabetes. Indeed, the authors have demonstrated the correlation between the tibial nerve cross-sectional area (CSA) and the severity of neuropathy [1]. Herein, we would like to comment on their Figure 2 which represents transverse ultrasound imaging to measure the tibial nerve CSA.…”
Section: Hindsight For Ultrasound Imaging/measurement Of the Tibial N...mentioning
confidence: 99%
“…We have read with great interest the article recently published in the European Journal of Neurology by Dhanapalaratnam et al [1].…”
Section: Hindsight For Ultrasound Imaging/measurement Of the Tibial N...mentioning
confidence: 99%
See 1 more Smart Citation
“…We are grateful to Ricci et al for their interest in our work [ 1 ]. They make valid points on limitations of peripheral nerve ultrasonography and measurement of cross‐sectional area (CSA) in individual patients, particularly where there may be anatomical variations.…”
mentioning
confidence: 99%
“…The sonographer must be aware of local anatomy and avoid taking measurement at the bifurcation site to avoid false representation of CSA. As described in Methods, we took measurements at 5 cm proximal to the medial malleolus [ 1 ]. Three measurements were taken at this site from each observer, and the mean value was used for data analysis.…”
mentioning
confidence: 99%